Polysilicon Process Development – The Effect Of PECVD Process Parameters On The Film Characteristics - Mujahidun Mashuri (Universiti Malaysia Perlis, 2008)
Thin polycrystalline silicon film has been used in the wide range of applications in the production of integrated circuits and other electronic products. Traditionally, polycrystalline silicon is deposited using Low Pressure Chemical Vapor Deposition (LPCVD) process at temperatures around 600 – 700C. This high temperature deposition process limits its application in the advanced device fabrication technology, which required a much lower processing technology or the so called thermal budget. This project studied the feasibility of using a lower temperature deposition technique, called Plasma Enhanced Chemical Vapor Deposition (PECVD) which deposited an amorphous silicon precursor film, at temperatures ranging from 100 – 300 C. This film is then to be converted to polycrystalline structure using a short heat treatment. The effect of PECVD process parameters which include the deposition temperature, RF power and chamber pressure on film characteristics is investigated. It was found that the deposition temperature and RF power have the most important impact on the film physical quality, and the film sheet resistivity is significantly reduced after short heat treatment.